PDS, National Food Security Act, and COVID-19 - Boss, Ruchira; Pradhan, Mamata; Roy, Devesh; Saroj, Sunil (International Growth Centre, 2021)
Introduced in 2013, the National Food Security Act (NFSA) brought about fundamental reforms in the public distribution system (PDS) and most importantly, declared a legal ‘right to food’. Based on a primary survey in Bihar, Odisha, and Uttar Pradesh, this article traces the changes in the PDS post NFSA, and during the Covid-19 crisis.